In vitro scavenging capacity of Organic Silicium (oral anti-aging) against reactive oxygen and nitrogen species - de Lima, Cláudio Moreira; Serafini, Mairim Russo; Rabelo, Thallita Kelly; Lima, Bruno dos Santos; Gelain, Daniel Pens; Quitans-Junior, Lucindo José; Cardoso, Juliana Cordeiro; Araújo, Adriano Antunes de Souza (Scientia Plena, 2014)
Reactive oxygen and nitrogen species can cause oxidative damage to biomolecules, eventually leading to many chronic diseases, aging, and other degenerative diseases in humans. In this context, Exsynutriment® is an oral anti-aging supplement based on organic silicium, which, according to the company, promotes the renovation of the conjunctive tissue, restructuring the skin sustainment fibers. The aim of this study was therefore to evaluate the redox properties of Exsynutriment®. It was evaluated in vitro redox tests as TRAP/TAR (non-enzymatic antioxidant potential), TBARS (lipoperoxidation), hydroxyl (OH-) and nitric oxide (.NO.) scavenging and SOD-like and CAT-like activity. The TRAP/TAR was determined using a method based on the chemiluminescence induced by the peroxyl radical generation initiated by AAPH. The Exsynutriment ® solution in the concentration 1 mg/mL showed a significant reduction in the effectiveness of CL induced by AAPH. Thiobarbituric acid reactive species (TBARS) assay was employed to measure the antioxidant capacity of Exsynutriment® in lipids incubated with AAPH and 2-deoxyribose degradation assay was employed to assesses the hydroxyl scavenging activity. Both the assays all doses tested had no effect against lipoperoxidation and did not reduce deoxyribose oxidative damage. However, nitric oxide radical generated from sodium nitroprusside was inhibited by all concentrations tested. The capacity of Exsynutriment® to interact with and/or scavenge/quench H2O2 and superoxide radicals in vitro was evaluated, respectively, by the catalase-like and the superoxide dismutase-like reaction assays. Our results did not show a significant variation to CAT and SOD-like activity. Results of the study showed no significant variation in such trials. Through the results we conclude that the organic silicium used as oral anti-aging showed antioxidant activity in vitro tests TRAP / TAR and nitric oxide (NO) scavenging, suggesting that future studies may elucidate chemical mechanisms.